A Cross-sectional Analysis Investigating Organizational Factors That Influence Near-Miss Error Reporting Among Hospital Pharmacists. Issue 2 (June 2016) - Patterson, Mark E.; Pace, Heather A.
Abstract : Objective: Underreporting near-miss errors undermines hospitals' ability to improve patient safety. The objective of this analysis was to determine the extent to which punitive work climate, inadequate error feedback to staff, or insufficient preventative procedures are associated with decreased frequency of near-miss error reporting among hospital pharmacists. Methods: Survey data were obtained from the Agency of Healthcare Research and Quality 2010 Hospital Survey on Patient Safety Culture. Near-miss error reporting was defined using a Likert scale response to the question, "When a mistake is made, but is caught and corrected before affecting the patient, how often is this reported?" Work climate, error feedback to staff, and preventative procedures were defined similarly using responses to survey questions. Multivariate ordinal regressions estimated the likelihood of agreeing that near-miss errors were rarely reported, conditional upon perceived levels of punitive work climate, error feedback, or preventative procedures. Results: Pharmacists disagreeing that procedures were sufficient and that feedback on errors was adequate were more likely to report that near-miss errors were rarely reported (odds ratio [OR], 2.5; 95% confidence interval [CI], 1.7–3.8; OR, 3.5; 95% CI, 2.5–5.1). Those agreeing that mistakes were held against them were equally likely as those disagreeing to report that errors were rarely reported (OR, 0.84; 95% CI, 0.61–1.1). Conclusions: Inadequate error feedback to staff and insufficient preventative procedures increase the likelihood that near-miss errors will be underreported. Hospitals seeking to improve near-miss error reporting should improve error-reporting infrastructures to enable feedback, which, in turn, would create a more preventative system that improves patient safety.